On the Robustness of Minimum Wage Effects: Geographically-Disparate Trends and Job Growth Equations - John T. Addison; McKinley L. Blackburn; Chad Cotti (Institute for the Study of Labor (IZA), 2014)
Just as the standard two-way fixed effects model for estimating the impact of minimum wages on employment has been sharply criticized for its neglect of spatial heterogeneity so, too, have the latest models been attacked for their uncritical use of state- or county-specific linear trends (and other spatial counterfactuals). Further attenuation of the effects of policy is also alleged to obtain in such circumstances where the true effect of minimum wages is upon employment growth rather than levels. This paper investigates whether such considerations call into question our earlier findings of statistically insignificant employment effects for an archetypal low-wage sector. We report that a continued focus on employment levels is indicated and that while experimentation with nonlinear trends may be productive their use is unlikely to dislodge the finding of considerably reduced negative employment effects.
Keywords: J23; J38; 330; minimum wages; employment; employment change; spatial controls